2018
DOI: 10.18632/oncotarget.23929
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analyses identify prognostic biomarkers for pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive malignancy. Here we show that shotgun and targeted protein sequencing can be used to identify potential prognostic biomarkers in formalin-fixed paraffin-embedded specimens from 9 patients with PDAC with “short” survival (<12 months) and 10 patients with “long” survival (>45 months) undergoing surgical resection. A total of 24 and 147 proteins were significantly upregulated [fold change ≥2 or ≤0.5 and P<0.05; or different detection frequencies (≥5 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 93 publications
1
31
1
Order By: Relevance
“…2). It is noted that the relationship between expression level of CLIC3 and prognosis were opposite to the previous reports [13][14][15][16][17], although the types of cancer are different. In fact, expression level of CLIC3 was negatively correlated with pathological tumor depth (Table 1).…”
Section: No Effects Of Clic3 Overexpression On Migration and Invasioncontrasting
confidence: 78%
See 1 more Smart Citation
“…2). It is noted that the relationship between expression level of CLIC3 and prognosis were opposite to the previous reports [13][14][15][16][17], although the types of cancer are different. In fact, expression level of CLIC3 was negatively correlated with pathological tumor depth (Table 1).…”
Section: No Effects Of Clic3 Overexpression On Migration and Invasioncontrasting
confidence: 78%
“…On the other hand, it has been reported that chloride intracellular channel 3 (CLIC3) plays roles as not only a soluble protein, but also an organellar membrane protein [10][11][12]. Moreover, CLIC3 is associated with poor prognosis in pancreatic cancer, breast cancer, ovarian cancer, and malignant pleural mesothelioma [13][14][15][16][17]. Taken together, we have raised two questions: (1) Does CLIC3 act as a Cl − channel in the membrane?, and (2) Page 2 of 11 Kawai et al J Physiol Sci (2020) 70:15 Is CLIC3 expression associated with prognosis of gastric cancer?.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous mass spectrometry-based study, we identified galectin 4 as a down-regulated protein in short-term survivors of pancreatic cancer [10]. The present study aimed to elucidate the prognostic role of galectin 4 in a large cohort of patients with resectable pancreatic cancer.…”
Section: Introductionmentioning
confidence: 88%
“…Protein expression patterns in PDAC liver metastases also have the potential to reveal new associations with clinical outcomes or identify novel therapeutic targets (14,31). With the understanding that PDAC is not a singular disease, we hypothesized that associations between protein expression and patient survival might display subtype-specific characteristics.…”
Section: Association Between Individual Protein Expression and Survivmentioning
confidence: 99%